2023
DOI: 10.1021/acsomega.3c00270
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of an Injectable Star-polylactide/Thiolated Hyaluronate Hydrogel as a Double Drug-Delivery System for Cancer Treatment

Abstract: Unsatisfactory solid-tumor penetration or rapid metabolism of nanomaterials limits their therapeutic efficacy. Here, we designed an injectable thiolated hyaluronate (HA-SH) hydrogel as a stable drugreleasing platform for in situ tumor treatment. Biodegradable star-shaped polylactide (S-PLLA) was first synthesized and fabricated to porous microspheres to encapsulate hydrophobic curcumin (Cur@S-PLLA), which was then blended with hydrophilic doxorubicin (Dox) and the HA-SH precursor to form composite in situ form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Other synthetic polymer hydrogels : Hydrogels composed of synthetic polymers such as polyethylene oxide, 260 polylactic acid, 261 and polypropylene fumarate 262 offer tunable mechanical strengths, but these materials typically suffer from poor biocompatibility and inadequate cell adhesion properties. Additionally, their rapid degradation and potential toxic byproducts can be significant drawbacks, further limiting their in vivo applications.…”
Section: Hydrogels For Cell Therapymentioning
confidence: 99%
“…Other synthetic polymer hydrogels : Hydrogels composed of synthetic polymers such as polyethylene oxide, 260 polylactic acid, 261 and polypropylene fumarate 262 offer tunable mechanical strengths, but these materials typically suffer from poor biocompatibility and inadequate cell adhesion properties. Additionally, their rapid degradation and potential toxic byproducts can be significant drawbacks, further limiting their in vivo applications.…”
Section: Hydrogels For Cell Therapymentioning
confidence: 99%
“…Toxicity laboratory studies proved that the composite systems could retain the drug for a longer period and showed more favorable anticancer properties compared to the nanoparticle system. Therefore, it can be suggested that the composite injectable gel containing nanoparticles can be a candidate for the local drug release that can fill the vacuum formed when removal of the solid tumor is carried out surgically 44 . Over prefabricated scaffolds, injectable in‐situ formed ones have many benefits.…”
Section: Introductionmentioning
confidence: 99%